Barriers to Growth: Analyzing the Development Challenges in Uzbekistan’s Stock Market - Sherzod Botirjonov (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
This thesis explores the multifaceted barriers obstructing the growth and advancement of Uzbekistan’s stock market. By scrutinizing regulatory hurdles, economic constraints, investor sentiments, technological limitations, and cultural factors, this study aims to provide a comprehensive understanding of the challenges restraining the expansion and efficiency of the stock market in Uzbekistan. Through an in-depth analysis of these impediments and proposing actionable strategies, this research contributes to the discourse on fostering a resilient and flourishing stock market ecosystem in Uzbekistan, thereby fostering broader economic growth and prosperity.